2003
DOI: 10.1080/09638280310001596487
|View full text |Cite
|
Sign up to set email alerts
|

Health status and functional capacity in a group of successfully ageing 65 – 85 year olds

Abstract: The role of activity is important in the study of successful ageing. This study reported gender and age group differences in the activities chosen, demonstrating that the inclusion of a cross-section of daily activities is essential in the study of health status and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
1
17
0
2
Order By: Relevance
“…En tal sentido, al enfocarse en la prueba TUG se observa una tendencia de mejor rendimiento de los hombres respecto a las mujeres entre los 60 y 80 años. Sin embargo, en los octogenarios esto disminuye, lo cual podría obedecer a dos factores: las características funcionales de quienes han logrado un envejecimiento exitoso [28][29][30] y haber preservado condiciones similares al efecto deletéreo acumulado por la edad 18 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En tal sentido, al enfocarse en la prueba TUG se observa una tendencia de mejor rendimiento de los hombres respecto a las mujeres entre los 60 y 80 años. Sin embargo, en los octogenarios esto disminuye, lo cual podría obedecer a dos factores: las características funcionales de quienes han logrado un envejecimiento exitoso [28][29][30] y haber preservado condiciones similares al efecto deletéreo acumulado por la edad 18 .…”
Section: Discussionunclassified
“…Es decir, aquellos AM categorizados ya sea como autovalentes sin riesgo, autovalentes con riesgo o riesgo de dependencia, además de marcar sus diferencias de su condición funcional otorgada por el instrumento EFAM, también expresan las diferencias de rendimiento en las tres pruebas producto de la edad (Tabla 4, Figuras 2 y 3). Lo anterior podría explicarse dado que los AM clasificados como autovalentes sin riesgo corresponden a aquellos sujetos que han logrado un envejecimiento exitoso 30 , en consecuencia, controlaron los factores que atentan contra su funcionalidad, excepto el envejecimiento fisiológico, por tanto, la pérdida de desempeño funcional en dichas pruebas reflejarían principalmente al factor edad 31,32 . A su vez, aquellos AM que clasificaron como autovalentes con riesgo y especialmente los riesgo de dependencia, corresponden a sujetos que además de la edad, han incorporado facto-res adicionales tales como: morbilidad, estilos de vida, nivel educacional, contexto psicosocial (considerados para la clasificación de EFAM); los que actuarían como variables determinantes sobre el rendimiento en las pruebas, generando mayor variabilidad entre ellos 33,34 .…”
Section: Discussionunclassified
“…Of particular interest in this regard, are gender differences in terms of physical activity engagement. For example, due to factors such as menopausal transition (MT), there is evidence to suggest that older women are less likely to engage in physical activity than older men [23]. This in turn can compound stress levels and increase the risk of depression [24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, older women are more involved in domestic activities, while older men prefer outside household tasks (Desrosiers et al, 2003) or are engaged in leisure activities (Klumb & Baltes, 1999). Likewise, older men are more engaged in physical activities compared to older women of the same age (Fone & Lundgren-Lindquist, 2003). As for age differences, it has been found that persons older than 75 years become more prone to engage in passive activities such as watching TV or reading (Desrosiers et al, 2003;Fone & Lundgren-Lindquist, 2003).…”
mentioning
confidence: 99%
“…Likewise, older men are more engaged in physical activities compared to older women of the same age (Fone & Lundgren-Lindquist, 2003). As for age differences, it has been found that persons older than 75 years become more prone to engage in passive activities such as watching TV or reading (Desrosiers et al, 2003;Fone & Lundgren-Lindquist, 2003).…”
mentioning
confidence: 99%